Early discharge and hospital-assisted home care is associated with better neurodevelopmental outcome in preterm infants. (October 2021) - Losbar, Jennifer-Laurence; Montjaux, Nathalie; Ehlinger, Virginie; Germany, Laurence; Arnaud, Catherine; Tscherning, Charlotte
Abstract: Aims: To compare hospital-assisted neonatal home care and standard hospital care for preterm newborns on neurodevelopment at 2 years corrected age, as well as duration of hospitalization, breastmilk rates, and readmissions before 1 year. Methods: This observational study enrolled 415 inborn neonates <34 + 6 weeks that received home care (2008 to 2015) in the French University Hospital of Toulouse and 3186 neonates from the national cohort of infants discharged in 2011 that received standard hospital neonatal care (EPIPAGE 2). Neurodevelopment at 2 years was assessed with the Ages and Stages Questionnaire-3 (ASQ-3). Results: At two years corrected age, infants in home care had 61% less risk of overall low ASQ ≤220 (OR = 0.4 [0.3–0.5], p < 0.001) and 31–80% less risk of low scores in four out of five domains compared to standard care. Home care was associated with shorter hospital stays (− 9 days; p < 0.001), higher breastmilk rates at final discharge (OR = 3.6 [2.8–4.6], p < 0.001 for singletons and OR = 2.3 [1.6–3.1], p < 0.001 for multiples), and more breastmilk feeding for at least six months (OR = 1.8 [1.3–2.3], p < 0.001 for singletons, OR = 3.6 [2.1–6.3], p < 0.001 for multiples). Readmissions also occurred less frequently with home care than with standard care, except for twins (OR = 0.7 [0.6–0.8], p < 0.001). Conclusion: Hospital-assisted neonatal home care for preterm infants was associated with better neurodevelopment at 2 years corrected age, shorter duration of hospitalization, and higher rates of breastmilk feeding at 6 months. Highlights: Hospital-assisted neonatal home care for preterm infants is a safe alternative to standard hospital care. Our study found the home care program was associated with a better neurodevelopmental outcome at 2 years corrected age. We confirmed a shorter duration of hospitalization and higher breast milk feeding rates at 6 months of age with home care.